2002
DOI: 10.1086/342479
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Dose Prolonged Intermittent Interleukin‐2 Adjuvant Therapy: Results of a Randomized Trial among Human Immunodeficiency Virus–Positive Patients with Advanced Immune Impairment

Abstract: Twenty-two patients with CD4(+)cell counts Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 59 publications
4
51
1
1
Order By: Relevance
“…As far as the clinical relevance of these findings is concerned it should be pointed out that studies on adjuvant immune therapy in patients with HIV infection usually include patients with CD4ϩ cell counts below 200 cells/l, because these patients are considered advanced immune impaired. 29 In patients after preoperative chemoradiotherapy we observed CD4ϩ cell counts as low as 200 cells/l on Days 1 and 2 after surgery. Therefore, it seems that these patients may also be considered advanced immune impaired.…”
Section: Discussionmentioning
confidence: 77%
“…As far as the clinical relevance of these findings is concerned it should be pointed out that studies on adjuvant immune therapy in patients with HIV infection usually include patients with CD4ϩ cell counts below 200 cells/l, because these patients are considered advanced immune impaired. 29 In patients after preoperative chemoradiotherapy we observed CD4ϩ cell counts as low as 200 cells/l on Days 1 and 2 after surgery. Therefore, it seems that these patients may also be considered advanced immune impaired.…”
Section: Discussionmentioning
confidence: 77%
“…Based on the Wilhem et al case report, we selected IL-2 at 600 000 IU/day as this was the lowest, well-tolerated dose that produced a significant and undelayed increase in CD4 + cell counts [14].We increased the dose as tolerated to achieve CD4 + counts greater than 300 cells/mm 3 , but unlike other case reports we titrated based on a three doses per week regimen, because of the patient's preference. The weekly 11 million IU (divided into three doses) our patient received exceeded the 7 million IU weekly (1 million daily) that Wilhem et al reported and was fewer than the intermittent doses used in HIV trials [14,[24][25][26][27] ( Table 1).…”
Section: Discussionmentioning
confidence: 79%
“…Interestingly, our patient appeared to have a prolonged immunological laboratory response to IL-2 therapy 6 months following IL-2 discontinuation; however, this effect appears to have diminished in the most recent laboratory results. The reason for this observation may include the differing dosage amount and scheduling of our patient's IL-2 regimen compared with other ICL case reports and HIV studies [12][13][14][15][24][25][26][27]. Continued out-patient monitoring will be required to elucidate more fully the durability of the clinical and immunological response.…”
Section: Discussionmentioning
confidence: 99%
“…Highly active antiretroviral therapy (HAART) induces a substantial control of HIV viral replication [53], but it allows for only a partial immune reconstitution, thus prompting the rationale for the adjuvant use of immunomodulants. Based on its in vitro action as a major T cell growth factor, interleukin (IL)-2 has now been extensively investigated for its potential to correct the HIV-driven immune deficiencies, possibly translating into immunological control over HIV infection.…”
Section: Interleukin-2 Adjuvant Therapymentioning
confidence: 99%